The Effectiveness of Training Methods to Improve Dribbling Learning Outcomes in Class XI Students of Senior High School Kristen Dobo - Ztella Rumawatine; Sanci Seltit (UNIVERSITAS NEGERI MAKASSAR, 2022)
The purpose of the study was to apply the exercise method in physical education learning to improve dribbling learning outcomes in class XI of SMA Kristen Dobo, Maluku. The research method used is quantitative with classroom action research design carried out 3 times in cycle I and cycle II through the stages of planning, implementation, observation, and reflection. The population of this study was class XI MIPA, SMA Kristen Dobo and the sample used was 56 students. The sampling technique used cluster sampling. Data collection on the results of learning to dribble in football games was analyzed qualitatively and quantitatively. The results showed that the use of training methods can improve the learning outcomes of dribbling. There is a significant increase in learning outcomes of dribbling in soccer games by 50% (completed) and increasing in the second cycle with a percentage of 88% (completed). Through the training method in physical education learning, students are more active and provide a positive response to the learning process so that students more easily understand dribbling well.